2019
DOI: 10.1002/jor.24421
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Stomal Microbiota of a Percutaneous Osseointegrated Prosthesis: A Longitudinal Prospective Cohort Study

Abstract: Percutaneous osseointegrated (OI) prostheses (POPs) are used to skeletally attach artificial limbs in amputees. While any permanent percutaneous interface is at risk of becoming infected by the resident microbiota colonizing the stoma, most of these patients remain infection-free. Avoidance of infection likely depends upon a mechanically and/or biologically stable skin-to-implant interface. The ultimate question remains, "why do some stomata become infected while others do not?" The answer might be found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 48 publications
5
19
1
3
Order By: Relevance
“…Although this should be regarded as an incomplete structural barrier, the surrounding host defence provides an additional functional barrier in situations with infection and breach of the structural barrier [42,48]. A local, and possible permanent, change in the stomal microbiota following the implantation of percutaneous, bone-anchored prostheses in humans has been demonstrated, both for limb prostheses [19,49] and the BAHS [27,29]. These studies confirmed colonisation by pathogens, typically Staphylococcus spp., at the implant sites, and often, these findings were independent from traditional clinical signs of infection [19,27].…”
Section: Discussionmentioning
confidence: 63%
“…Although this should be regarded as an incomplete structural barrier, the surrounding host defence provides an additional functional barrier in situations with infection and breach of the structural barrier [42,48]. A local, and possible permanent, change in the stomal microbiota following the implantation of percutaneous, bone-anchored prostheses in humans has been demonstrated, both for limb prostheses [19,49] and the BAHS [27,29]. These studies confirmed colonisation by pathogens, typically Staphylococcus spp., at the implant sites, and often, these findings were independent from traditional clinical signs of infection [19,27].…”
Section: Discussionmentioning
confidence: 63%
“…Ten veteran unilateral transfemoral amputees, who were recruited to participate in an FDA-approved Early Feasibility Study of a POP device (NCT02720159), were also included in this current study (NCT02564432) with IRB approval (#00073178). The study design, described in detail previously [ 19 ], is briefly outlined below. A (Level II) prospective, longitudinal, observational study was conducted where participating patients underwent two separate surgical procedures to fit a transfemoral percutaneous OI implant [DJO global, Austin, TX] with a wait time of 6–8 weeks between procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Dabei ist es jedoch nicht zielführend, auf Bakterienfreiheit zu therapieren. Im Gegenteil ist sogar bekannt, dass der Stomakanal und die Öffnung des Stomas nach der Etablierung des Stomas sofort mit Bakterien besiedelt werden [27] und diese sogar einen protektiven Charakter besitzen können. Baktierennachweise im Stoma sind nicht mit Infektion gleichzusetzen und in gewissem Maße physiologisch [27].…”
Section: Diskussionunclassified
“…Im Gegenteil ist sogar bekannt, dass der Stomakanal und die Öffnung des Stomas nach der Etablierung des Stomas sofort mit Bakterien besiedelt werden [27] und diese sogar einen protektiven Charakter besitzen können. Baktierennachweise im Stoma sind nicht mit Infektion gleichzusetzen und in gewissem Maße physiologisch [27]. In einer 12-monatigen Untersuchung der Besiedelungsdynamik an TOPS-Stomata konnte Beck et al feststellen, dass im Vergleich zur umgebenden Haut des Oberschenkels, Staphylococcus aureus (S.aureus) im Stoma signifikant häufiger auftrat [27] obwohl keine Infektion oder Weichteilirritation vorlag.…”
Section: Diskussionunclassified
See 1 more Smart Citation